Financial Statement Model Based on SAK EMKM In The “Polife” Student Entrepreneur Group - Kumaat, Lusye Corvanty; Paendong, Yelly Sjenny; Lintong, Jerry Sonny (Indonesian Journal of Social Science Research, 2021)
The purpose of this research is to create a Financial Report Model based on SAK-EMKM in the Student Entrepreneurial Group "PROLIFE" in Manado City, North Sulawesi Province. The ratio of the number of entrepreneurs or entrepreneurs in Indonesia is currently only 2 percent of the total population. Ideally, the ratio of entrepreneurs is 4 percent in order to encourage national economic growth. The POLIFE student entrepreneurial group is part of the Student Entrepreneurship Program (SEP) which is a program initiated by the Ministry of Education and Culture of the Republic of Indonesia, to be developed into campus life in order to stimulate the entrepreneurial spirit of students. As an entity, the manager is obliged to prepare financial reports, which will be used by interested parties in making decisions. To help MSMEs meet their financial reporting needs, the Indonesian Institute of Accountants' Financial Accounting Standards Board has compiled and ratified SAK EMKM. Financial reports based on SAK EMKM, which Polife must prepare, consist of a statement of financial position, an income statement, and notes to financial statements.